Pengaruh Catur Purusa Artha, Love Of Money, Machiavellian, dan Kesesuaian Kompensasi terhadap Kecenderungan Fraud Akuntansi pada LPD Se-Kecamatan Tejakula - Ngurah Suyasa Jaya Putra; I Putu Julianto; Diota Prameswari Vijaya (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the influence of Catur Purusa Artha, Love of Money, Machiavellianism, and compensation suitability on the tendency of accounting fraud in Village Credit Institutions (LPDs) throughout Tejakula District. This research is motivated by the occurrence of fraud cases in several LPDs in Bali, highlighting the importance of fraud prevention through cultural, psychological, and organizational approaches. The study employs a quantitative approach based on the Fraud Triangle Theory. The population consists of LPD management personnel in Tejakula District, while the sample was selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that Catur Purusa Artha has a negative effect on the tendency of accounting fraud. The higher the implementation of the values of dharma, artha, kama, and moksha, the lower the tendency of individuals to engage in fraudulent behavior. In contrast, Love of Money and Machiavellianism have positive effects on the tendency of accounting fraud. Compensation suitability also has a negative effect on the tendency of accounting fraud. These findings suggest that local cultural values, individual characteristics, and compensation systems play important roles in reducing the risk of accounting fraud in LPDs.